Performance improvement of AlGaN-based ultraviolet light-emitting diodes by amending inverted-Y-shaped barriers with alternate doped Si and Mg. (July 2017) - Hou, Yufei; Guo, Zhiyou; Liu, Yang; Guo, Min; Huang, Jing; Yao, Shunyu; Zhang, Xiu; Gong, Xing; Xu, Zhihong
Abstract: The effect of using inverted-Y-shaped barriers with alternate doped Si and Mg in traditional AlGaN-based ultraviolet light-emitting diodes (UV-LEDs) has been investigated through APSYS simulation program. The results indicated that the specially designed UV-LED has better light output power and internal quantum efficiency (IQE) compared with the conventional AlGaN barriers and the AlGaN composition-graded barriers. Efficiency droop of the new structure reduced to 2.17% while 41.73% in conventional LED. In addition, alternating doped Si and Mg in AlGaN composition-graded barriers obviously improves the hole injection efficiency, modulate carrier distribution and suppress electron spill out from active region, and thus enhances the carrier radiation recombination rate, ameliorate IQE and optical output power. Highlights: The inverted-Y-shaped barrier can significantly alleviate the electron leakage. The special designed barrier can improve the hole injection efficiency. Mg acceptors can be ionized due to the oscillation at Mg-doped QB and enhance the hole concentration. Si-doped QBs could increase electron concentration and improve the interfacial qualities of the DUV-LED.